2010
DOI: 10.1093/jac/dkq412
|View full text |Cite
|
Sign up to set email alerts
|

Burden of antimicrobial resistance in European hospitals: excess mortality and length of hospital stay associated with bloodstream infections due to Escherichia coli resistant to third-generation cephalosporins

Abstract: Morbidity and mortality attributable to third-generation-cephalosporin-resistant E. coli BSI is significant. If prevailing resistance trends continue, high societal and economic costs can be expected. Better management of infections caused by resistant E. coli is becoming essential.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
135
1
6

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 215 publications
(148 citation statements)
references
References 38 publications
6
135
1
6
Order By: Relevance
“…This pathogen is the one of the most frequently isolated in both community and hospital-acquired urinary tract infections, and could be the cause of severe or fatal outcomes associated with bacteraemia, which has been shown to be increasing in France [27], with a significant increase in incidence of ESBL-E bacteraemia between 2009 and 2013 from 0.021 to 0.044 per 1,000 PD, respectively. The burden of ESBL-E bacteraemia, including E. coli, was reported in studies in several European counties (Austria, Belgium, Croatia, England, Germany, Greece, Ireland, Italy, Latvia, Malta, Romania, Scotland and Slovenia) in 2008 [26] and, more specifically, in Switzerland in 2009 to be five to seven excess days in hospital per hospital stay, at a cost of about 8,000 Euros per bacteraemia episode [2].…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…This pathogen is the one of the most frequently isolated in both community and hospital-acquired urinary tract infections, and could be the cause of severe or fatal outcomes associated with bacteraemia, which has been shown to be increasing in France [27], with a significant increase in incidence of ESBL-E bacteraemia between 2009 and 2013 from 0.021 to 0.044 per 1,000 PD, respectively. The burden of ESBL-E bacteraemia, including E. coli, was reported in studies in several European counties (Austria, Belgium, Croatia, England, Germany, Greece, Ireland, Italy, Latvia, Malta, Romania, Scotland and Slovenia) in 2008 [26] and, more specifically, in Switzerland in 2009 to be five to seven excess days in hospital per hospital stay, at a cost of about 8,000 Euros per bacteraemia episode [2].…”
Section: Discussionmentioning
confidence: 98%
“…During this time, E. coli was the major pathogen among ESBL-E, especially in intensive-care units, where the incidence was double that seen in all other settings. Indeed, ESBL-E. coli poses a potential threat of high burden to HCF and related facilities (such as nursing homes and homebased hospital care) [2,26]. This pathogen is the one of the most frequently isolated in both community and hospital-acquired urinary tract infections, and could be the cause of severe or fatal outcomes associated with bacteraemia, which has been shown to be increasing in France [27], with a significant increase in incidence of ESBL-E bacteraemia between 2009 and 2013 from 0.021 to 0.044 per 1,000 PD, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…In a single-center retrospective study, Tumbarello et al 35 found that ESBL production in E. coli causing BSI was associated with an excess LOS of 7 days and a cost of i5,026 (CHF 7,634 in 2009). De Kraker et al 36 performed a multicenter prospective matched cohort study involving 13 European hospitals and estimated an excess LOS of 5 days attributable to third-generation cephalosporin resistance in BSIs caused by E. coli. While both are otherwise robust studies, we would contend that neither the direct comparison of post-BSI-onset LOS between ESBL and non-ESBL BSI used by the former study or the matching and adjustment used by the latter adequately account for time-dependent bias.…”
Section: Discussionmentioning
confidence: 99%
“…1,5 Antibiotic resistance is a major threat to public health worldwide. 6,7 There are high prevalence of multi drug resistant E. coli in UTI infections against β-Lactam groups (penicillins, cephalosporins, carbapenems and Monobactams) because of their ability to produce Extended Spectrum β-Lactamases (ESBLs). 8,9 E. coli may acquire other antibiotic resistance traits from surroundings bacteria and conversely it can spread its resistance genes to different potential pathogens.…”
Section: Introductionmentioning
confidence: 99%